Analysis of renal impairment in MM-003: a phase III study of pomalidomide + low-dose dexamethasone versus high-dose dexamethasone in refractory or relapsed and refractory multiple myeloma - Weisel, Katja; Goldschmidt, Hartmut (Haematologica, 2016)
Pomalidomide + low-dose dexamethasone is effective and well tolerated for refractory or relapsed and refractory multiple myeloma after bortezomib and lenalidomide failure. The phase III trial MM-003 compared pomalidomide + low-dose dexamethasone with high-dose dexamethasone. This subanalysis grouped patients by baseline creatinine clearance ≥ 30 − < 60 mL/min (n=93, pomalidomide + low-dose dexamethasone; n=56, high-dose dexamethasone) or ≥ 60 mL/min (n=205, pomalidomide + low-dose dexamethasone; n=93, high-dose dexamethasone). Median progression-free survival was similar for both subgroups and favored pomalidomide + low-dose dexamethasone versus high-dose dexamethasone: 4.0 versus 1.9 months in the group with baseline creatinine clearance ≥ 30 − < 60 mL/min (P<0.001) and 4.0 versus 2.0 months in the group with baseline creatinine clearance ≥ 60 mL/min (P<0.001). Median overall survival for pomalidomide + low-dose dexamethasone versus high-dose dexamethasone was 10.4 versus 4.9 months (P=0.030) and 15.5 versus 9.2 months (P=0.133), respectively. Improved renal function, defined as an increase in creatinine clearance from < 60 to ≥ 60 mL/min, was similar in pomalidomide + low-dose dexamethasone and high-dose dexamethasone patients (42% and 47%, respectively). Improvement in progression-free and overall survival in these patients was comparable with that in patients without renal impairment. There was no increase in discontinuations of therapy, dose modifications, and adverse events in patients with moderate renal impairment. Pomalidomide at a starting dose of 4 mg + low-dose dexamethasone is well tolerated in patients with refractory or relapsed and refractory multiple myeloma, and of comparable efficacy if moderate renal impairment is present. This trial was registered with clinicaltrials.gov identifier 01311687 and EudraCT identifier 2010-019820-30.